Positive Association Between Serum Alkaline Phosphatase and First Stroke in Hypertensive Adults - Zhang, Yuanyuan; Li, Huan; Xie, Di; Li, Jianping; Zhang, Yan; Wang, Binyan; Liu, Chengzhang; Song, Yun; Wang, Xiaobin; Huo, Yong; Hou, Fan Fan; Xu, Xiping; et al. (Frontiers in Cardiovascular Medicine, 2021)
The relation of alkaline phosphatase (ALP) with stroke risk remains uncertain. We aimed to investigate the association between serum ALP and the risk of first stroke, and explore possible effect modifiers, in hypertensive adults. This is a post hoc analysis of the China Stroke Primary Prevention Trial (CSPPT). A total of 19,747 participants with baseline ALP measurements and without liver disease at baseline were included. The primary outcome was first stroke. Over a median of 4.5 years, there was a positive association between serum ALP and the risk of first stroke (per SD increment, adjusted HR, 1.10; 95%CI: 1.01, 1.20). When serum ALP was assessed as quartiles, a higher risk of first stroke was found in participants in quartile 2-4 (ALP ≥79 IU/L; adjusted HR, 1.38; 95% CI: 1.11, 1.71), compared with those in quartile 1 (ALP <79IU/L). Similar trends were found for first ischemic stroke and first hemorrhagic stroke. Similar results were also found in participants with a normal range of baseline serum ALP (20-140 IU/L) levels (per SD increment, adjusted HR, 1.15; 95%CI: 1.05, 1.27). In Chinese hypertensive adults, our study suggests that higher serum ALP levels, even in normal range, were significantly associated with increased risk of first stroke and first ischemic stroke.